Libby loves science : states of matter - Derting, Kimberly; Johannes, Shelli R. (I can read book., 2024)
Libby loves science -- and experimenting! In this Level 3 I Can Read! title, Libby and her classmates are excited to welcome a new student into their classroom. When the ice cream for the welcome party melts, Libby is curious to see how the three states of matter can save the celebration. Experiment with Libby and find out!